Efektivitas Pengelolaan Zakat Perusahaan dalam Mengurangi Kesenjangan Ekonomi: Perspektif Muamalah - Muhammad Alfian; Randi Shodik; Muhammad Sauqi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study aims to analyze the effectiveness of corporate zakat management in reducing economic inequality from the perspective of muamalah. The research employs a library research method with a qualitative-descriptive approach by examining various literature sources, empirical data, and regulations related to corporate zakat in Indonesia. The findings reveal that corporate zakat management achieves optimal effectiveness when zakat funds are distributed through a productive zakat scheme. This scheme is implemented through six main stages: preliminary surveys of beneficiaries, regular assistance, provision of business capital, business partner guidance, motivational training, and periodic evaluations of beneficiaries’ business development. However, practical implementation still faces several challenges. The allocation of funds for business capital among economically disadvantaged communities has only reached approximately 0.4%, while the majority of zakat funds, around 97.1%, are still utilized for consumptive assistance. This condition indicates that the economic empowerment function of zakat has not yet been fully optimized. Therefore, integrative solutions are required, including institutional strengthening through the establishment of Islamic microfinance units such as Baitul Maal wat Tamwil (BMT) internally, as well as stronger government regulations through tax deductible incentive policies externally to support the sustainable optimization of corporate zakat distribution.